DEVELOPMENTAL CONTROL OF SOME PHYSIOLOGICAL FACTORS ON REPRODUCTIVE BIOLOGY AND RUDIMENTARY EMBRYOS PHENOMENON IN CARROT SEEDS - Aseel M.H. H. Al-Khafaji,; Kadhim D. H. Al-jubouri, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate delayed germination and immature embryos of carrot seeds; This research was implemented at vegetable field of College of Agricultural Engineering Sciences - University of Baghdad during two sequent seasons (fall and spring). The experiment was conducted using factorial within Randomized Complete Block Design arrangement with three factors and replicates (3X3X2). The aqueous barley sprouts extract (B0, B1) (0, 100 g.L-1) represented the first factor. Trehalose (T0, T1, T2) (0, 50, 75 mmole.L-1) represented the second factor. Calcium (C0, C1, C2) (0, 1, 2 ml.L-1) represented the third factor. Results showed the effectiveness of third order interaction treatment B1T2C1 in increasing germination speed and percent for the seeds of royal umbel (92, 97%); secondary umbel (90.67, 94.67%); and tertiary umbel (75.68, 86.33%). The mentioned treatment increased embryo length for the seeds of primary (royal) umbel (1628.3 µm), secondary umbel (1620.3 µm); and tertiary umbel (874.7 µm ). in compare with  the lowest percents that found in B0T0C2 treatment.